2023
DOI: 10.1038/s41598-023-29678-7
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of global potential suitable habitats of Nicotiana alata Link et Otto based on MaxEnt model

Abstract: Nicotiana alata Link et Otto, widely used in landscaping, is not only of great ornamental value but also of high commercial and medical value. The global potential habitat of N. alata and the environmental factors affecting its distribution are not that clear at present. To provide a reference for the reasonable and extensive planting of N. alata now and in the future, the MaxEnt model was used to predict its global suitable habitats under current and future climate conditions, respectively, based on global ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…In line with findings from previous research, it is crucial to recognize that, apart from climate, elevation exerts a significant influence on species distribution [48], while soil composition also contributes to shaping species distributions [49].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In line with findings from previous research, it is crucial to recognize that, apart from climate, elevation exerts a significant influence on species distribution [48], while soil composition also contributes to shaping species distributions [49].…”
Section: Discussionsupporting
confidence: 65%
“…The results revealed that bio 16 and bio 5 were the most significant predictors influencing the distribution of Acacia senegal, as shown in Table 3. [48,49] According to our findings, approximately 25.4% of Sudan's Gum Arabic area is potentially suitable for Acacia senegal, and for the period of 2021-2100, approximately 46% to 62% of the area is potentially suitable for SSP2-4.5, whereas the new suitable area ranges from 13.5% to 17.1%. Significant increases were projected under future climatic 2100 scenarios, with several currently unsuitable areas becoming suitable under all the climatic models.…”
Section: Discussionmentioning
confidence: 68%
“…The value of Vi at a specific point, P, during a given period is denoted by “pi”, and “fi” signifies the percentage of points in the study area where Vi is less than “pi” [ 68 ]. The calculation of the MESS values was based on the following criteria: (1) when fi = 0, the MESS was calculated as 100 × (p − mini)/(maxi − mini), indicating the lower limit of environmental suitability; (2) for values of fi between 0 and 50, the MESS was 2 fi, suggesting a gradient of increasing similarity; (3) for fi values greater than 50 and less than 100, the MESS was 2 × (100 − fi), reflecting a gradient of decreasing similarity; and (4) when fi = 100, the formula was modified to 100 × (maxi − pi)/(maxi − mini), indicating the upper limit of environmental suitability [ 69 , 70 , 71 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the study of species distribution, environmental variables are the main leading factors of species niches at large spatial scales [53,54]. We selected 37 environmental variables that may affect the growth distribution of D. involucrata and predicted the current and future suitable distribution areas in our study.…”
Section: Environmental Datamentioning
confidence: 99%